The prognostic implications of podoplanin in cancer‐associated fibroblasts and PD‐L1 expression in high‐grade neuroendocrine carcinoma of the lung - Tatsuya Miyamoto; Tomohiro Haruki; Karen Makishima; Shinji Matsui; Yuki Oshima; Yoshihisa Umekita; Hiroshige Nakamura (Thoracic Cancer)
Abstract Objectives Podoplanin (PDPN) expression in cancer‐associated fibroblasts (CAFs) (CAF‐PDPN) is considered a poor prognostic factor in nonsmall cell lung cancer, but little is known about its clinical significance in high‐grade neuroendocrine carcinoma of the lung (HGNEC). This study examines the association between CAF‐PDPN and stromal programmed death‐ligand 1 (PD‐L1) expression and the prognostic implications of CAF‐PDPN and PD‐L1 expression status in surgically resected HGNEC patients. Methods Immunohistochemical analyses were performed on 121 resected HGNEC specimens using antibodies against PDPN and PD‐L1. Correlations between CAF‐PDPN, stromal PD‐L1 expression, and clinicopathologic features and their implications for survival were analyzed statistically. Results There were substantially more large‐cell neuroendocrine carcinomas in the stromal PD‐L1‐positive group and more vascular invasion in the tumoral PD‐L1‐positive group. PDPN expression in CAF was moderately correlated with stromal PD‐L1 expression (ρ = 0.567, p < 0.001). In a survival analysis combining CAF‐PDPN and stromal PD‐L1 status, the 5‐year RFS rates for Group A: CAF‐PDPN (+)/stromal PD‐L1 (+), Group B: CAF‐PDPN (+)/stromal PD‐L1 (−), Group C: CAF‐PDPN (−)/stromal PD‐L1 (+), and Group D: CAF‐PDPN (−)/stromal PD‐L1 (−) were 62.0%, 46.8%, 17.5%, and 20.2%, respectively, with corresponding 5‐year OS rates of 76.6%, 69.2%, 27.0%, and 25.3%. The log‐rank test showed statistically significant differences among the groups in RFS (p < 0.001) and OS (p < 0.001). Conclusions There is a correlation between CAF‐PDPN and tumoral/stromal PD‐L1 expression, and positive status for either CAF‐PDPN or stromal PD‐L1 expression could be an independent favorable prognostic factor in surgically resected HGNEC patients.